Preparation method of hydroxylated boron nanosheets / MXene and its humidity sensing application

The OBNS/MXene composite was prepared by template method and vacuum freeze-drying method, which solved the problem of poor humidity sensing performance in the prior art, achieved high sensitivity and stability, and was suitable for a wide range of humidity detection and human physiological signal monitoring.

CN117185296BActive Publication Date: 2024-12-24NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310787355.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-24
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

It is difficult to prepare stable, low-cost, and low-temperature derivatives with high humidity sensing properties, and humidity sensing is rarely studied.

Method used

OBNS/MXene composites were prepared by template method and vacuum freeze-drying method. By assembling boron hydroxylated nanosheets and MXene at room temperature, hollow spherical and ribbon superstructures were formed, which improved humidity sensing performance and was used for the preparation of humidity sensors. .

Benefits of technology

It achieves high sensitivity, short response and recovery time, low humidity hysteresis, long-term stability and strong hydrophilicity, and is suitable for humidity detection of 11% RH-97% RH, and can be used for non-invasive human physiological signal monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185296B_ABST
    Figure CN117185296B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method of a boron nanosheet composite material and its application in humidity sensing detection, belonging to the technical field of nanocomposite material preparation. Using methylated boron nanosheets and MXene as precursors, a hydroxylated boron nanosheet (OBNS) / MXene composite is prepared by further adopting a template method and a vacuum freeze-drying method. Secondly, the prepared OBNS / MXene composite is dissolved in a mixed solvent of methanol and water, and then the mixture is dripped on a gold interdigital electrode, where only the electrodes at both ends are exposed on the surface of the gold interdigital electrode, and the rest of the parts are covered with a sensing material, so as to obtain a humidity sensor with a humidity detection range of 11%RH-97%RH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a composite material based on hydroxylated boron nanosheets. The prepared composite material based on hydroxylated boron nanosheets has excellent humidity sensing performance and belongs to the technical field of nanocomposite material preparation. Background Art

[0002] The excellent properties of borophene that are generally known indicate its broad application prospects, but its electron-deficient structure means that borophene cannot exist independently and stably. Researchers have proposed using a metal substrate to balance the charge so that the charge is redistributed to obtain stable borophene. However, such synthesis methods often require high temperature, ultra-high vacuum and other conditions, with complicated steps, harsh conditions and high costs. Borophene derivatives can not only improve the stability of the system but also retain the properties of borophene itself, which lays the foundation for the application of borophene derivatives. At present, borophene derivatives can be prepared by liquid phase selective etching, ion exchange, exfoliation and molecular beam epitaxy.

[0003] According to the applicant, humidity is of great significance to human activities such as medical care, industrial manufacturing and climate monitoring. Humidity can serve as a bridge between respiration and sensor signals, and can reflect human health status by non-invasively monitoring human respiratory rate and breathing depth. Non-invasive remote real-time respiratory monitoring not only reduces the pain of patients, but also provides convenience for medical staff. Therefore, it has become a top priority to prepare a resistive humidity sensor with high humidity response, fast response / recovery time, low hysteresis and good stability. At present, there are literatures reporting the performance of boron-based composite materials, but there are few related studies on humidity sensing of boron-based composite materials. Summary of the invention

[0004] In order to solve the above technical problems, the technical solution proposed in the present invention is: the OBNS / MXene composite is prepared by the template method and vacuum freeze-drying method. The hollow spherical and ribbon-like superstructures in the composite are assembled by OBNS and MXene. The surface of the composite contains abundant oxygen-containing functional groups, which improves its humidity sensing performance and is used for the preparation of humidity sensors. The OBNS / MXene humidity sensor of the present invention shows ultra-high sensitivity, short response and recovery time, good long-term stability, low hysteresis, etc. in humidity detection.

[0005] In order to solve the technical problem of the present invention, the proposed technical solution is: a method for preparing a boron nanosheet / MXene composite humidity sensing material, comprising the following steps:

[0006] (1) Dissolving methylated boron nanosheets in water at room temperature, shaking to allow the product to fully react, centrifuging at 5000 rpm for 5 min, and taking the upper layer of the bubble solution to obtain hydroxylated boron nanosheets OBNS;

[0007] (2) MXene is prepared by liquid phase selective etching, and after the reaction, it is washed with oxygen-free water until the pH is 6-7;

[0008] (3) The mass concentration of MXene prepared in (2) added in step (1) is 0.5 mg / mL, V OBNS :V MXene =20:1, pre-freeze in liquid nitrogen for 3-5 minutes, perform vacuum freeze-drying and then take out at room temperature to obtain OBNS / MXene composite material.

[0009] Preferably, the preparation method of the methylated boron nanosheets in step (1) is to use magnesium boride, concentrated hydrochloric acid, methanol and iodine as raw materials, synthesize by liquid phase selective etching method, the molar ratio of methylated boron nanosheets to water is 0.005:1, and the reaction temperature is 25-28°C.

[0010] Preferably, the preparation method of MXene in step (2) is to use MAX, concentrated hydrochloric acid and lithium fluoride as raw materials, react in a 40° C. water bath for 24 hours, and after the reaction, wash the product with oxygen-free water until the pH is 6-7.

[0011] Preferably, in step (3), the product is pre-frozen at a low temperature of -196°C for 3-5 minutes, and the vacuum freeze-drying time is 24 to 48 hours.

[0012] Preferably, 0.005 g of methylated boron nanosheets is weighed and placed in a 2 mL centrifuge tube containing 1 mL of deionized water. The product is shaken to fully react, and obvious hydrogen bubbles can be seen. The evenly dispersed solution is centrifuged at 5000 rpm for 5 min, and the upper bubble solution is taken. 0.5 mg / mL 50 μL MXene solution is added to the centrifuge tube containing the upper bubble solution and shaken evenly. The mixture is pre-frozen in liquid nitrogen at a low temperature of -196°C for 3-5 min, and then the pre-frozen solution is placed in a vacuum freeze dryer and frozen for 24 h. After being taken out at room temperature, the OBNS / MXene composite is obtained.

[0013] In order to solve the technical problem of the present invention, another technical solution is proposed: an OBNS / MXene composite having a three-dimensional hollow sphere structure and a one-dimensional band structure prepared by the preparation method.

[0014] In order to solve the technical problem of the present invention, another technical solution is proposed: application of the OBNS / MXene composite material to a humidity sensor with a humidity detection range of 11% RH-97% RH.

[0015] Preferably, the OBNS / MXene complexes with a three-dimensional hollow sphere structure and a one-dimensional band structure are respectively dispersed in a mixed solution of methanol and water to obtain corresponding concentrated dispersions, the volume ratio of methanol: water being 1.5:1, and the concentrated dispersion of the OBNS / MXene complex is evenly dropped on the cleaned interdigitated electrodes and on the gold cross electrodes, and dried naturally to form a film, with only the electrodes at the two ends exposed on the surface of the gold cross electrodes, and the rest of the parts are all covered with sensing materials to obtain a humidity sensor.

[0016] Preferably, sensors are used to monitor human physiological signals, non-contact humidity sensing and respiration at fingertips, and the sensors are combined with a back-end circuit containing a Bluetooth module to build a wireless respiration monitoring platform.

[0017] Beneficial effects of the present invention:

[0018] OBNS / MXene materials were prepared using methylated boron nanosheets and MXene as precursors. The surfaces of OBNS and MXene both contain a large number of oxygen-containing functional groups and have good hydrophilicity. By designing the size and morphology of the composite, a structure with three-dimensional hollow spheres and one-dimensional microbelts was obtained. The above two structures can provide a large specific surface area, and the three-dimensional hollow spheres can fully expose hydrophilic adsorption sites. These two points are conducive to the rapid transport of water molecules on the surface of the material, making it have a higher humidity response, so the OBNS / MXene composite can be used for the preparation of humidity sensors.

[0019] 1. The preparation of the OBNS / MXene composite of the present invention improves the stability of the material and increases the specific surface area of ​​the material.

[0020] 2. The OBNS / MXene humidity sensor of the present invention can detect humidity under different relative humidity environments at room temperature.

[0021] 3. The OBNS / MXene humidity sensor of the present invention exhibits ultra-high sensitivity, short response and recovery time, good long-term stability, low hysteresis, etc. in humidity detection.

[0022] 4. The OBNS / MXene humidity sensor of the present invention can realize non-invasive monitoring of human physiological signals. When it is combined with a back-end circuit containing a Bluetooth module, a wireless real-time monitoring platform can be constructed.

[0023] 5. After the methylated boron nanosheets are mixed with water, a surface reaction will occur, generating a small amount of boric acid and releasing H2 gas (reference reaction equation: 2B+6H2O→2B(OH)3+3H2↑). At the same time, a large number of hydroxyl groups are attached to the surface, forming hydroxylated boron nanosheets. Since H2 gas has low solubility in aqueous solution, bubbles will form. OBNS and MXene (<1μm) gather around the bubbles to form spherical aggregates, which are then vacuum-freezed to form hollow spherical structures, fully exposing the hydrophilic active sites of the above two materials, providing favorable conditions for high adsorption and rapid transport of water molecules. Large-diameter MXene and a small amount of OBNS form a one-dimensional ribbon structure, providing more hydrophilic active sites. Therefore, OBNS / MXene is a highly hydrophilic material.

[0024] 6. Analyze the above test results, such as Figure 5 As shown in the figure, the dynamic response diagram of the OBNS / MXene composite sensor and the MXene sensor under the same humidity environment, in which the resistance value decreases with the increase of humidity. Under the same humidity environment (97% RH), the humidity response value of the OBNS / MXene composite sensor is 2000 times that of the MXene humidity sensor, which has strong hydrophilic activity.

[0025] like Figure 6 As shown, the OBNS humidity sensor alone cannot collect signals on the signal collector due to its poor conductivity. The response value of the OBNS / MXene composite sensor is 2000 times that of the MXene sensor.

[0026] like Figure 7 As shown, the water contact angle of the OBNS / MXene composite sensor is the smallest at 15.6°, the water contact angle of OBNS is 31.5°, and the water contact angle of MXene is 56.7°, proving that the OBNS / MXene composite sensor has the strongest hydrophilicity.

[0027] 7. If Fig.17 As shown, under the same humidity environment, when the volume ratio of MXene to OBNS is 1:20, the highest humidity response is shown. That is, in Example 1, the volume of OBNS is 1 mL, and MXene is 0.5 mg / mL, 50 μL.

[0028] 8. The OBNS / MXene composite material prepared in Example 1 was dissolved in methanol, water, methanol: water = 1:1, methanol: water = 1.5:1 (the above ratios are all volume ratios) respectively. The results showed that the film-forming property was best when the composite material was dispersed in a solvent of methanol: water = 1.5:1. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below in conjunction with the accompanying drawings.

[0030] Figure 1 This is the SEM image of the OBNS / MXene composite in Example 1.

[0031] Figure 2 TEM image of the OBNS / MXene composite in Example 1.

[0032] Figure 3 (a) is the full XPS spectrum of the OBNS / MXene composite in Example 1, (b) is the B1s high-resolution spectrum of the OBNS / MXene composite and OBNS in Example 1, (c) is the C1s high-resolution spectrum of the OBNS / MXene composite and MXene, and (d) is the Ti 2p high-resolution spectrum of the OBNS / MXene composite and MXene.

[0033] Figure 4 FTIR images of OBNS, MXene and OBNS / MXene composite in Example 1.

[0034] Figure 5 This is the dynamic response curve of the OBNS / MXene humidity sensor and MXene in Example 3 under the same humidity environment.

[0035] Figure 6 These are the dynamic response curves of the OBNS sensor, MXene sensor, and OBNS / MXene sensor in Example 3 under the same humidity environment.

[0036] Figure 7 (a) is the water contact angle characterization test diagram of MXene, (b) OBNS, and (c) OBNS / MXene in Example 3.

[0037] Figure 8 (a) is the dynamic response diagram of the OBNS / MXene humidity sensor in Example 3 under different humidity environments and (b) is the response value fitting curve.

[0038] Fig. 9 Response and recovery time diagram of the OBNS / MXene humidity sensor in Example 3 under high humidity (RH 84%) and room temperature (T=25°C) environments.

[0039] Fig.10 (a) is the dynamic response recovery diagram of the OBNS / MXene humidity sensor in Example 3 under different humidity environments, and (b) is the adsorption and analysis curves of the sensor at the corresponding humidity.

[0040] Fig.11This is the long-term stability test diagram of the OBNS / MXene humidity sensor in Example 3.

[0041] Fig.12 This is the Nyquist curve of the OBNS / MXene humidity sensor in Example 3 at different humidity and room temperature (T=25°C).

[0042] Fig.13 (a) Nyquist curve of OBNS / MXene humidity sensor in Example 3 at different temperatures and the ln(σT / S cm -1 K) vs. T -1 / 10 -3 K -1 )’s linear fitting plot.

[0043] Fig.14 (a) is the non-contact humidity sensing of the OBNS / MXene humidity sensor at different distances from the wet fingertip in Example 3 and (b) is the humidity sensing dynamic curve diagram when the wet fingertip is 8 mm away from the sensor.

[0044] Fig.15 This is a dynamic curve diagram of the OBNS / MXene humidity sensor monitoring three breathing modes in Example 3.

[0045] Fig.16 Schematic diagram of the wireless respiratory monitoring platform of the OBNS / MXene humidity sensor in Example 3.

[0046] Fig.17 This is the humidity dynamic response curve of OBNS and MXene in different proportions in Comparative Example 1. DETAILED DESCRIPTION

[0047] In order to better understand the present invention, the technical solution of the present invention is specifically described below through specific embodiments in conjunction with the accompanying drawings.

[0048] Example 1: Preparation method of OBNS / MXene composite

[0049] MgB2 powder (0.5g, >99%, Sigma-Aldrich) and I2 (0.3g, >99%, Aladdin Chemical Reagent Co., Ltd.) were added to 10mL methanol (>99.8%, ACS grade, Aladdin Chemical Reagent Co., Ltd.) and ultrasonicated until the iodine beads were fully dissolved. The mixture was placed in an environment of 3-7°C for 1h, and then 0.1mL, 4mol / LHCl was added dropwise to the mixture. The mixture was placed at room temperature and stirred in a water bath for one week until the color of the iodine completely faded. The product after the reaction was taken out to wash away the residual impurities, methanol was added to the product and centrifuged at 10000rpm for 5min, the operation was repeated four times or more, and then ultrasonicated for half an hour to separate the stacked boron layers to obtain thinner methylated boron nanosheets.

[0050] Weigh 0.005 g of methylated boron nanosheets into a 2 mL centrifuge tube containing 1 mL of deionized water, shake to allow the product to react fully, and obvious hydrogen bubbles can be seen. The evenly dispersed solution is centrifuged at 5000 rpm for 5 min, and the upper layer of bubble solution is taken to prepare OBNS.

[0051] Weigh 3g LiF and add it to 30mL HCl. After stirring for 10min, weigh 1g MAX and add it slowly in batches. Adjust the speed to 800r and the temperature to 40℃ for water bath reaction for 24h. Centrifuge the product at 7000rpm for 5min, pour out the supernatant, add 10mL, 10wt% HF and shake for 10min, then pour out the supernatant, and then add oxygen-free water to wash the product until the pH is 6-7 to obtain MXene.

[0052] At room temperature, add the MXene solution into a centrifuge tube containing OBNS and shake it evenly. Pre-freeze the mixture in liquid nitrogen at low temperature (-196°C) for 3-5 minutes, then put the pre-frozen solution into a vacuum freeze dryer and freeze it for 24 hours. After taking it out at room temperature, the OBNS / MXene composite was obtained.

[0053] The product in Example 1 was analyzed. Figure 1 As shown, the SEM image of the OBNS / MXene composite shows that the obtained product is a three-dimensional hollow sphere and a two-dimensional ribbon-like composite structure.

[0054] The product in Example 1 was analyzed. Figure 2 As shown, the TEM image of the OBNS / MXene composite shows that the hollow spheres are close to the two-dimensional bands, all of which are at the micron level.

[0055] The product in Example 1 was analyzed. Figure 3As shown, the XPS graph of the OBNS / MXene composite shows that charge transfer occurs on the surface of the OBNS / MXene composite, there is interaction, and elements such as F and O exist.

[0056] The product in Example 1 was analyzed. Figure 4 As shown, the FTIR image of the OBNS / MXene composite shows that the FTIR image of the OBNS / MXene composite has a large number of oxygen-containing functional groups on the surface and has strong hydrophilicity.

[0057] Example 2: Method for preparing humidity sensor based on OBNS, MXene, and OBNS / MXene composite

[0058] (1) Take 4 mg of the OBNS / MXene composite prepared in Example 1 and disperse it in 1 mL of a mixed solution of methanol: water (1.5:1) to prepare a corresponding concentrated dispersion. The concentrated dispersion of the OBNS / MXene composite is evenly dripped on the cleaned interdigitated electrodes and on the gold cross electrodes, and dried naturally to form a film. Only the electrodes at the two ends are exposed on the surface of the gold cross electrodes, and the rest of the parts are all covered by the sensing material, thereby preparing a humidity sensor based on the above OBNS / MXene composite material.

[0059] (2) Take 50 μL of 0.5 mg / mL MXene aqueous solution, evenly drop it on the cleaned interdigital electrode and the gold cross electrode, and dry it naturally to form a film. Only the electrodes at the two ends are exposed on the surface of the gold cross electrode, and the rest of the area is covered with the sensing material, thus obtaining a humidity sensor based on the above composite material.

[0060] (3) Take 4 mg of OBNS powder and disperse it in 1 mL of a mixed solution of methanol: water (1.5:1) to prepare the corresponding concentrated dispersion. The concentrated dispersion of OBNS is evenly dropped on the cleaned interdigitated electrode and the gold cross electrode, and naturally dried to form a film. Only the electrodes at the two ends are exposed on the surface of the gold cross electrode, and the rest of the area is covered with the sensing material, thereby obtaining a humidity sensor based on the above-mentioned OBNS / MXene composite material.

[0061] (4) Prepare the humidity required for the experiment. Use saturated salt solutions containing LiCl, CH3COOK, MgCl2, K2CO3, NaBr, KI, NaCl, KCl and K2SO4 to prepare relative humidity of 11%, 22%, 33%, 43%, 57%, 68%, 75%, 84% and 97% respectively. Under room temperature conditions, the relative humidity of the air above the saturated solution of metal salts is constant (at room temperature, the relative humidity of the air above the saturated solution of NaBr is 57% RH). Use dry silica gel as a desorption bottle, and bottles containing different saturated salt solutions as humidity bottles.

[0062] (5) Connect the wire to the device and place it in a dry silica gel bottle. At this time, the other end of the wire is connected to the Keysight 34972A data acquisition device to test the resistance signal of the device. The resistance change value of the OBNS / MXene composite sensor during the change of external humidity can be tested. The relative humidity range during the test is 11% RH-97% RH.

[0063] Example 3: Application of OBNS / MXene composite humidity sensor - testing different relative humidity

[0064] (1) The OBNS / MXene composite sensor prepared in Example 1 was placed in a dry silica gel bottle, connected with a wire and connected to a Keysight 34972A data acquisition device. At room temperature, the sensor was placed in different humidity bottles to collect response signals under different humidity environments.

[0065] (2) Place the sensor in a dry silica gel bottle and measure the baseline resistance R0 of the humidity sensor.

[0066] (3) Determination of resistance R at different relative humidity g , the humidity detection range gradually increases from 11% RH to 97% RH.

[0067] (4) Under each humidity environment, the resistance of the sensor decreases as the humidity increases and returns to its initial resistance when placed in a dry silica gel bottle.

[0068] (5) The measured resistance is converted to R0 / R g , where R0 is the baseline resistance at no relative humidity (10% RH), and R g It is the resistance value in different relative humidity environments.

[0069] (6) R0 / R g Plotted against time, as humidity increases, the resistance change increases accordingly.

[0070] Analyze the above test results, such as Figure 5As shown in the figure, the dynamic response diagram of the OBNS / MXene composite sensor and the MXene sensor under the same humidity environment, in which the resistance value decreases with the increase of humidity. Under the same humidity environment (97% RH), the humidity response value of the OBNS / MXene composite sensor is 2000 times that of the MXene humidity sensor, which has strong hydrophilic activity.

[0071] like Figure 6 As shown, the OBNS humidity sensor alone cannot collect signals on the signal collector due to its poor conductivity. The response value of the OBNS / MXene composite sensor is 2000 times that of the MXene sensor.

[0072] like Figure 7 As shown, the water contact angle of the OBNS / MXene composite sensor is the smallest at 15.6°, the water contact angle of OBNS is 31.5°, and the water contact angle of MXene is 56.7°, proving that the OBNS / MXene composite sensor has the strongest hydrophilicity.

[0073] like Figure 8 As shown in the figure, the dynamic response curves of the OBNS / MXene composite sensor under different humidity environments, and the response within five cycles showed a significant decrease, indicating that the OBNS / MXene composite sensor has good cycle stability. When the humidity increases from 10% RH to 97% RH, the response value of the OBNS / MXene composite sensor is 2.3*10 3 , showing a high humidity response. The response values ​​in different relative humidity environments were fitted, and the linear relationship was good, R 2 =0.99.

[0074] like Fig. 9 As shown, the response and recovery time diagram of the OBNS / MXene composite sensor at RH 84% and room temperature indicates that the humidity sensor has ultra-fast response time and recovery time, with a response time of 3.6s and a recovery time of 3.9s.

[0075] like Fig.10 As shown in the figure, the dynamic response diagram of the OBNS / MXene composite sensor under different humidity environments and the adsorption analysis curve diagram made of the corresponding response values, the adsorption analysis curves almost overlap, indicating that the sensor exhibits obvious moisture hysteresis.

[0076] like Fig.11 As shown, the OBNS / MXene composite sensor was placed in the air, and the response values ​​under different humidity environments were measured. The sensor was placed in the air for 40 days, and the response value of the sensor did not show a significant decrease. The results showed that the sensor has good long-term stability.

[0077] like Fig.12 As shown in Figure 2, the impedance values ​​of the OBNS / MXene composite sensor measured at different humidity levels. As the humidity increases, the conductivity of the sensor increases.

[0078] like Fig.13 As shown in the figure, the impedance values ​​of the OBNS / MXene composite sensor at different temperatures were measured in the same humidity environment (RH80%). As the temperature rises, the conductivity increases, and the activation energy of the OBNS / MXene composite sensor is calculated to be 0.95eV using the Arrhenius equation for the ESI data, which is judged to be an on-board mechanism.

[0079] like Fig.14 As shown, the response values ​​of the OBNS / MXene composite sensor to different distances from the wet fingertip. As the distance increases, the response value decreases, indicating that the sensor can identify different distances from the fingertip.

[0080] like Fig.15 As shown in the figure, the dynamic response diagram of the OBNS / MXene composite sensor monitoring human breathing. Under different breathing modes, the sensor shows different response strengths and response frequencies, indicating that the sensor can identify three breathing modes: fast, normal and deep breathing, and can identify a breathing mode with a cycle of 0.8s, showing high sensitivity.

[0081] like Fig.16 As shown in the figure, the schematic diagram of the wireless respiratory monitoring platform constructed by combining the OBNS / MXene composite sensor with the back-end circuit containing a Bluetooth module shows that the sensor can realize wireless real-time respiratory monitoring, laying the foundation for subsequent applications in the field of health monitoring.

[0082] Therefore, it can be said that the OBNS / MXene composite can be used for the preparation of humidity sensors and has excellent humidity sensing performance.

[0083] Table 1 Comparison of the performance of OBNS / MXene composites and existing materials

[0084]

[0085] Comparative Example 1

[0086] Weigh 5 mg of methyl-functionalized boron nanosheets and place them in a 2 mL centrifuge tube. Add 1 mL of deionized water and shake evenly to make it fully react. Centrifuge at 5000 rpm for 5 min to take the upper mixed solution containing bubbles. Take different volumes of MXene (0.5 mg / mL) solution prepared in Example 1 and add them to the above mixed solution centrifuge tube containing bubbles, taking 100 μL, 50 μL, and 33 μL respectively.

[0087] like Fig.17 As shown, under the same humidity environment, when the volume ratio of MXene to OBNS is 1:20, the highest humidity response is shown. That is, in Example 1, the volume of OBNS is 1 mL, and MXene is 0.5 mg / mL, 50 μL.

[0088] Comparative Example 2

[0089] The OBNS / MXene composite material prepared in Example 1 was dissolved in methanol, water, methanol: water = 1:1, methanol: water = 1.5:1 (the above ratios are all volume ratios) respectively. The results showed that the film-forming property was best when the composite material was dispersed in a solvent of methanol: water = 1.5:1.

[0090] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for preparing a boron nanosheet / MXene composite humidity sensing material, characterized in that: The steps include: (1) Under room temperature, dissolve methylated boron nanosheets in water, shake to allow the product to react fully, centrifuge at 5000 r for 5 min, and take the upper layer of bubble solution to obtain hydroxylated boron nanosheets OBNS; (2) Preparation of MXene Ti3C2T by liquid phase selective etching X After the reaction is completed, use oxygen-free water to wash until the pH is 6-7; (3) Add the MXene prepared in step (2) to step (1), the mass concentration of MXene is 0.5 mg / mL, V OBNS :V MXene = 20:1, pre-freeze in liquid nitrogen for 3-5 min, perform vacuum freeze-drying and then take out at room temperature to obtain OBNS / MXene composite material.

2. The method for preparing the boron nanosheet / MXene composite humidity sensing material according to claim 1, characterized in that: The preparation method of the methylated boron nanosheets in step (1) is to use magnesium boride, concentrated hydrochloric acid, methanol and iodine as raw materials, synthesize by liquid phase selective etching method, the molar ratio of methylated boron nanosheets to water is 0.005:1, and the reaction temperature is 25~28°C.

3. The method for preparing the boron nanosheet / MXene composite humidity sensing material according to claim 1, characterized in that: The preparation method of MXene in step (2) is to use Ti3AlC2, concentrated hydrochloric acid and lithium fluoride as raw materials, react in a 40°C water bath for 24 hours, and after the reaction, wash the product with oxygen-free water until the pH value is 6-7.

4. The method for preparing the boron nanosheet / MXene composite humidity sensing material according to claim 1, characterized in that: In the step (3), the product is pre-frozen at a low temperature of -196°C for 3-5 minutes, and the vacuum freeze-drying time is 24-48 hours.

5. The method for preparing the boron nanosheet / MXene composite humidity sensing material according to claim 1, characterized in that: Weigh 0.005 g of methylated boron nanosheets and put them into a 2 mL centrifuge tube containing 1 mL of deionized water. Shake the solution to allow the product to react fully. Obvious hydrogen bubbles can be seen. Centrifuge the evenly dispersed solution at 5000 rpm for 5 min, take the upper bubble solution, add 0.5 mg / mL 50 μL MXene solution to the centrifuge tube containing the upper bubble solution, and shake evenly. Pre-freeze the mixture in liquid nitrogen at a low temperature of -196°C for 3-5 min, then put the pre-frozen solution into a vacuum freeze dryer and freeze it for 24 h. After taking it out at room temperature, the OBNS / MXene composite was obtained.

6. An OBNS / MXene composite having a three-dimensional hollow sphere structure and a one-dimensional ribbon structure prepared according to the preparation method according to any one of claims 1 to 5.

7. The use of the OBNS / MXene composite material according to claim 6, characterized in that: For humidity sensor applications with a humidity detection range of 11% RH - 97% RH.

8. The use of the OBNS / MXene composite material according to claim 6, characterized in that: The same mass of OBNS / MXene complex was dispersed in a mixed solution of methanol and water to prepare the corresponding concentrated dispersion. The volume ratio of methanol: water was 1.5:

1. The concentrated dispersion of OBNS / MXene complex was evenly dropped on the cleaned interdigital electrode and the gold cross electrode. It was naturally dried to form a film. Only the electrodes at the two ends were exposed on the surface of the gold cross electrode, and the rest of the parts were all covered by the sensing material to obtain a humidity sensor.

9. The use of the OBNS / MXene composite material according to claim 8, characterized in that: Sensors are used to monitor human physiological signals, non-contact humidity sensing and respiration at fingertips, and the sensors are combined with back-end circuits containing Bluetooth modules to build a wireless respiration monitoring platform.